Phase Equilibrium of Biologically Active Systems 4,6-dinitro-5,7-dichlorobenzofuroxane and 5-nitro-4,6-dichlorobenzofuroxane - L. M. Yusupova; A. N. Khuziakhmetova; E. G. Gorelova; V. K. Mingazova; I. V. Galkina (Разработка и регистрация лекарственных средств, 2020)
Introduction. One of the intensive ways to increase the therapeutic efficacy and safety of a drug is a combination of several already known substances or chemical compounds, leading to the appearance of a synergistic effect. This method of creating a medicinal product is one of the most important trends in recent times, since the synergistic effect allows one to achieve greater pharmacological activity, expand the range of medical applications and reduce the toxic effect of the drug on the organism. These pharmaceutical active substances include a binary mixture "Dimixan"(mixture 4,6-dinitro-5,7-dichlorobenzofuroxan (4,6-DNDHBFO) and 5-nitro-4,6-dichlorobenzofuroxan (5-NDHBFO). They demonstrate potentiated synergism to the ultra-resistant mold fungus of the species Aspergillius niger. However, the synergy mechanism of the mixture of 5-NDHBFO and 4,6-DNDHBFO is not fully studied. The results of determining the thermodynamic characteristics and phase equilibria in these systems will make it possible to determine the nature of the interaction between 5-NDCBPO and 4,6-DNDCBPO, which will undoubtedly contribute to the optimal organization of the production of a promising drug.Aim. Establishing the nature of the interaction between 5-NDHBFO and 4,6-DNDHBFO in the system.Materials and methods. Using differential scanning calorimetry (DSC), phase equilibria in the 5-NDHBFO and 4,6-DNDHBFO systems were studied in a wide range of component concentrations. From the state diagram, the thermodynamic characteristics of the eutectic were determined: the enthalpy and entropy of melting of mixtures of 5-NDHBFO – 4,6-DNDHBFO at different ratios of components.Results and discussion. Based on the results of the study, phase reactions with the physicochemical interaction of 5-NDHBFO and 4,6-DNDHBFO in two-component systems with the formation of eutectic alloys of the "solid solution" type are identified. The specific values of the enthalpies of melting of alloys of eutectic compositions were determined, from which the entropies of melting were calculated. The results of a study of the density of eutectic compositions of 5-NDHBFO – 4,6-DNDHBFO indicate the formation of an interstitial solid solution.Conclusion. The nature of the interaction between 5-NDHBFO and 4,6-DNDHBFO in the system, leading to the appearance of a synergy effect, has been established. The results obtained are important for predicting the eutectic compositions of 5-NDHBFO and 4,6-DNDHBFO as active pharmaceutical ingredient with increased biological activity.